Cystatin‐C and epicardial adipose tissue as noninvasive predictors of cardiovascular risk in acromegaly. (2nd December 2016) - Aulinas, Anna; Crespo, Iris; Viladés, David; Leta, Ruben; Urgell, Eulàlia; Biagetti, Betina; Webb, Susan M.; Valassi, Elena
Summary: Background: Acromegaly (ACRO) is associated with elevated cardiovascular risk, although the prevalence of coronary artery disease (CAD) is unclear. Increased epicardial adipose tissue (EAT) and elevated cystatin‐C (Cys‐C) levels are cardiovascular risk factors, also related to the progression of CAD in several populations. Aims: To measure the severity and extent of CAD in patients with ACRO and to determine whether either EAT or Cys‐C reflect higher cardiovascular risk in patients with ACRO than in healthy controls. Subjects and methods: Case–control study, of 35 patients with ACRO (19 males, 17 with active disease) and 35 age‐, gender‐ and body mass index (BMI)‐matched healthy controls; mean age was 48·1 ± 8·1 years and mean BMI was 27·6 ± 4·8 kg/m 2 . Cys‐C was measured by an immunoturbidimetric assay. The 10‐year risk of developing a coronary event was calculated using the Framingham Risk Score (FRS). EAT index (volume indexed to body surface area), and severity and extent of CAD were measured using a 256‐slice multidetector computed tomography scanner (iCT‐256 Philips Healthcare, Amsterdam). Results: Coronary artery disease lesions, EAT index and severity/extent of CAD were similar between patients with ACRO and controls. Forty‐four per cent of patients with ACRO had mild coronary lesions associated with greater EAT index (ß = 0·022, P = 0·036). Cys‐C levels correlated with both EAT index (ρ = 0·386, P = 0·031) and FRS (ρ = 0·477, P = 0·004) in patients with ACRO only, despite similar prevalence of traditional cardiovascular risk factors. In a multiple linear regression model, both Cys‐C levels (ß = 0·369, P = 0·007) and EAT index (ß = 0·29, P = 0·025) predicted FRS ( R 2 = 0·613). Conclusions: In patients with ACRO, both Cys‐C and EAT index might be used as noninvasive predictors of cardiovascular risk.